Anomalous electrical properties of poly vinyl alcohol films with Tb3+ ions and copper nanoparticles in different solvents - Kumar B.; Kaur G.; Singh P.; Rai S.B. (My University, 2025)
Laser ablation was used to fabricate copper nanoparticles (NPs) in different solvents from sodium lauryl sulphate, acetone and ethanol by applying 1064 nm radiation from a Nd:YAG laser. The sizes and shapes of the colloidal Cu NPs were investigated by transmission electron microscopy (TEM). The electrical conductivities of Tb3+ in polymer films with Cu NPs were measured in the frequency range of 20 Hz to 1 MHz and the temperature range of 308-343 K. It was found that the electrical conductivity of Tb3+ was greater for larger Cu NPs with sizes ranging from 20-40 nm in ethanol as compared to Cu NPs with smaller dimensions formed in the other two solvents. It was concluded that using ethanol as the solvent enhanced the electrical conductivity of Tb3+ in the polymer film. The activation energy as well as the variation in the loss tangent with temperature also explains the enhanced electrical conductivity. This journal is © The Royal Society of Chemistry 2015.